UKIRAN PATUNG KENYALANG DALAM KALANGAN MASYARAKAT IBAN DI SARAWAK - ROBSON PANGGABIAN, JUDI@GINDI (Universiti Malaysia Sarawak, (UNIMAS), 2016)
This research is about carving the Statue of Hornbills in Sarawak Iban community in Sarawak .. The statue is one of the famous sculptures in the Iban community. This is because the Statue of Hornbills are carved by the Iban community since time immemorial. The method used in this research is qualitative. The aim of this study was to identify the concept of carving Statue Iban community in Sarawak. Hornbill statue carved in the concept will be seen on the selection of motifs, the material used to carve and taboos related Statue Hornbills among the Iban community. This research also see thefunctional differences Statue carving hornbills in the past and now. The information collected and obtained from informants in longhouses Rampun Wie, Sri Aman. Research is also conducted on the management of the Statue of Hornbills in Sarawak Museum. Management assessed the management of the Statue of Hornbills in Sarawak Museum is the management of finance, human resources and marketing. Management assessed the effectiveness of management's use of the Sarawak Museum. Related information obtained from informants management of officers and staff of the Sarawak Museum. The findings prove that the inherent concept, management in museum and functional differences in the sculpture statue Hornbills in the Iban community in Sarawak.